Faith, finance, and technological legitimacy: the discourse of Sharia compliance in Indonesian fintech communication - Suaidi (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Indonesia’s Sharia fintech sector must reconcile religious normativity, financial intermediation, technological innovation, and consumer risk within a regulatory environment where only a small subset of licensed providers is classified as Sharia-based. Objective: This study examines how official Indonesian fintech communication constructs Sharia compliance as religious, institutional, technological, and financial legitimacy. Method: Using a qualitative corpus-assisted critical discourse design, this study analyses 19 publicly accessible documents issued between 2018 and 2026 by ALAMI, Ammana, Dana Syariah, OJK, DSN-MUI, Bank Indonesia, and AFTECH through lexical, legitimation, and multimodal interface analysis. Results: Findings show that Sharia legitimacy is primarily authorised through regulatory references, fatwas, ethical vocabulary, and named contracts, although detailed contractual explanation is less frequent than broad institutional alignment. Technological legitimacy is produced through claims of digital readiness, accessibility, efficiency, innovation, and transaction traceability, but concrete descriptions of technical safeguards remain comparatively limited. Implication: Trust is constructed alongside risk disclosure, creating a conditional legitimacy in which platforms promise transparency and inclusion while assigning users responsibility for prudent financial judgement. Novelty: This study contributes a multidimensional account of Sharia fintech discourse by demonstrating that compliance is communicatively assembled through intertwined religious authority, technological rationalisation, institutional recognition, and managed consumer risk within Indonesia’s rapidly evolving digital financial ecosystem today.